2016
DOI: 10.1002/app.44665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermoset soy protein resin toughening by natural rubber and epoxidized natural rubber

Abstract: Fully bio-based soy protein isolate (SPI) resins were toughened using natural rubber (NR) and epoxidized natural rubber (ENR). Resin compositions containing up to 30 wt % NR or ENR were prepared and characterized for their physical, chemical and mechanical properties. Crosslinking between SPI and ENR was confirmed using 1 H-NMR and ATR-FTIR. All SPI/NR resins exhibited two distinctive drops in their modulus at glass transition temperature (T g ) and degradation temperature (T d ) at around 250 and 215 8C, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…E-ERF 5 and E-ERF 10 show about 1.2 GPa and 1.1 GPa of modulus, and 52 MPa and 47 MPa of fracture strength, respectively, compared to that of neat epoxy resin having modulus of 1.4 GPa and tensile strength of 58 MPa. Compared to other studies, epoxy resin containing ENR particles (not in fiber form) showed much loss in tensile properties [24,51,52]. For example, epoxy resin with 12% liquid epoxidized natural rubber (particle size 0.48 to 0.67 in diameter) increased 125% impact toughness, but decreased tensile properties by 15 MPa from 65 MPa to 50 MPa, compared to neat epoxy resin [51].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…E-ERF 5 and E-ERF 10 show about 1.2 GPa and 1.1 GPa of modulus, and 52 MPa and 47 MPa of fracture strength, respectively, compared to that of neat epoxy resin having modulus of 1.4 GPa and tensile strength of 58 MPa. Compared to other studies, epoxy resin containing ENR particles (not in fiber form) showed much loss in tensile properties [24,51,52]. For example, epoxy resin with 12% liquid epoxidized natural rubber (particle size 0.48 to 0.67 in diameter) increased 125% impact toughness, but decreased tensile properties by 15 MPa from 65 MPa to 50 MPa, compared to neat epoxy resin [51].…”
Section: Resultsmentioning
confidence: 96%
“…The broad peak around 1600 cm −1 corresponds to NH 2 bending of excess amine group from the curing agent in the epoxy resin. Neat ERFs transmittance peaks at 751 cm −1 , 852 cm −1 and 1246 cm −1 corresponding to the oxirane groups appeared in the spectra [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zein protein has been recently used as a sustainable natural material in a wide variety of applications including resins for green composites, bioplastics, air filtration (in fiber form), food packaging (in film form), tissue engineering, and adhesive, due to its fully renewable and biodegradable nature and low cost. 1,2 However, in its pure form it suffers from brittleness and low resistance to crack propagation. In particular, crosslinked thermoset zein resins have been shown to possess poor toughness and resistance to crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…as natural rubber (NR) in the polymer resin has been a promising method. 1 Plant derived NR is also a biodegradable and fully sustainable material which possesses moderate tensile strength but good tear resistance, toughness and high resilience. 6 Due to its very low glass transition temperature (T g ) of about -65 °C and flexible backbone structure, NR is highly extensible at room temperature (RT) and makes it a desirable candidate for toughening purposes.…”
Section: Introductionmentioning
confidence: 99%